Analysis of Maternal Mortality Determinants in Bondowoso District, East Java - Fransiska, Ratna Diana; Respati, Supriyadi Hari; Mudigdo, Ambar (Journal of Maternal and Child Health, 2017)
Background: Data from Population Inter-Census Survey (Survei Penduduk Antar Sensus,